2014
DOI: 10.1111/ele.12378
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic conservatism in plant‐soil feedback and its implications for plant abundance

Abstract: We examined whether plant-soil feedback and plant-field abundance were phylogenetically conserved. For 57 co-occurring native and exotic plant species from an old field in Canada, we collected a data set on the effects of three soil biota treatments on plant growth: net whole-soil feedback (combined effects of mutualists and antagonists), feedback with arbuscular mycorrhizal fungi (AMF) collected from soils of conspecific plants, and feedback with Glomus etunicatum, a dominant mycorrhizal fungus. We found phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 51 publications
4
123
1
Order By: Relevance
“…The few plant-soil feedback experiments in a restoration context suggest that restoration of a soil community may be crucial for establishing late successional plant communities (e.g., De Deyn et al 2003, Kardol et al 2006, Middleton and Bever 2012 although success is not always observed (Kardol et al 2009). Much remains to be learnt about where feedbacks are likely to affect restoration success, including how closely related plants may be affected by soil biota (Anacker et al 2014).…”
Section: Restoring Species Composition Requires More Than Just Plantsmentioning
confidence: 99%
“…The few plant-soil feedback experiments in a restoration context suggest that restoration of a soil community may be crucial for establishing late successional plant communities (e.g., De Deyn et al 2003, Kardol et al 2006, Middleton and Bever 2012 although success is not always observed (Kardol et al 2009). Much remains to be learnt about where feedbacks are likely to affect restoration success, including how closely related plants may be affected by soil biota (Anacker et al 2014).…”
Section: Restoring Species Composition Requires More Than Just Plantsmentioning
confidence: 99%
“…Hence, while the effects of negative plant-soil feedback on the spatial structure of individual plants depend on the intensity of the underlying density-dependent mechanisms (Bagchi et al 2010), its ubiquitous presence suggests that plant-soil feedback may play an important role in the maintenance of plant diversity in natural (cm) communities (Mazzoleni et al 2015b). In a review on direct evidences on conspecific negative plant-soil feedback from both terrestrial and aquatic plants, Mazzoleni et al (2007) reported 138 cases of conspecific negative plant-substrate interactions, 96 of which are associated with grassland species, including Erigeron canadensis, one species of Veronica and one species of Viola, thus reinforcing the hypothesis that plant-soil feedbacks may contribute to the disruption of shortrange phylogenetic clustering (see also Anacker et al 2014).…”
Section: Discussionmentioning
confidence: 72%
“…Phylogenetic distance has been successfully used as a measure of ecological (dis)similarity and as a predictor of biotic interaction outcomes in studies that included plant species from multiple families (Anacker et al 2014;Parker et al 2015). It is likely that ecological differences in such studies may be influenced by deeply conserved traits that vary between families and therefore are phylogenetically determined.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-soil feedbacks on conspecifics vary with phylogenetic distance (Anacker et al 2014) and are affected by plant origin (Klironomos 2002) when phylogenetically diverse plant species were examined. However, it remains unknown if these explanatory variables also predict plant soil feedback differences between closely related plant species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation